The New Asylum and Transit Countries in Europe During and in the Aftermath of the 2015/2016 Crisis - Stoyanova, Vladislava (International Refugee Law Ser., 2018)
Understanding the realities of protection in a Europe that had failed to manage the crisis in asylum that unfolded in 2015 and 2016 requires a comprehension of how law shapes and distorts refugee protection practices in frontline states. In this collection Vladislava Stoyanova and Eleni Karageorgiou provide an essential cartography of the state of asylum during the crisis. The volume captures four dynamics: the absorption of EU norms in Central and South Eastern Europe; the reaction in this region to the massive movement of asylum seekers in 2015 and 2016; the initiation of normative developments in the area of asylum during and beyond the crisis by the countries in this region; and the question of solidarity.--